IMPLEMENTATION OF SWEDIA INDONESIA SUSTAINABILITY PARTNERSHIP (SISP) 2017-2021 - Mussada, Raka; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The sustainable development phenomenon Sweden-Indonesia Sustainability Partnership (SISP) aims to strengthen partnerships between stakeholders in Indonesia and Sweden in line with the 2030 Agenda. Sweden is leading the global transition towards innovative and sustainable solutions and can play an important role in Indonesia's ambition to achieve the goals of the 2030 Agenda, become a regional centre for manufacturing industries and become a high-income country. These ambitious targets, in line with President Jokowi's reform agenda, create significant opportunities for Swedish companies across the value chain. This research uses a Liberalism perspective and uses the nation state level of analysis. This study uses the theory of Development Theory, the conditions of development in this study refer to the theory by Todaro and Smith that development should be seen as a multidimensional process, which includes a variety of fundamental changes or social structures, public attitudes, and national institutions in addition to pursuing accelerated economic growth, addressing income inequality, and poverty alleviation through the Sweden-Indonesia Sustainability Partnership. The analysis will use official sources from the Ministry of Foreign Affairs, United Nations, BPK RI, and the Government Office of Swden. The research shows that the implementation of the Sweden-Indonesia Sustainability Partnership created by the Indonesian government and the Swedish government is the signing of four memoranda of understanding (MoUs) in the series of Sweden-Indonesia Sustainability Partnership events that took place on 6-8 December 2023 in Jakarta. Keywords: Sweden, Indonesia, Sustainable Development, Implementation, MoU.